Enhanced production of 3, 4‐dihydroxybutyrate from xylose by engineered yeast via xylonate re‐assimilation under alkaline condition. Issue 2 (9th November 2022) - Yukawa, Takahiro; Bamba, Takahiro; Matsuda, Mami; Yoshida, Takanobu; Inokuma, Kentaro; Kim, Jungyeon; Won Lee, Jae; Jin, Yong‐Su; Kondo, Akihiko; Hasunuma, Tomohisa
Abstract: To realize lignocellulose‐based bioeconomy, efficient conversion of xylose into valuable chemicals by microbes is necessary. Xylose oxidative pathways that oxidize xylose into xylonate can be more advantageous than conventional xylose assimilation pathways because of fewer reaction steps without loss of carbon and ATP. Moreover, commodity chemicals like 3, 4‐dihydroxybutyrate and 3‐hydroxybutyrolactone can be produced from the intermediates of xylose oxidative pathway. However, successful implementations of xylose oxidative pathway in yeast have been hindered because of the secretion and accumulation of xylonate which is a key intermediate of the pathway, leading to low yield of target product. Here, high‐yield production of 3, 4‐dihydroxybutyrate from xylose by engineered yeast was achieved through genetic and environmental perturbations. Specifically, 3, 4‐dihydroxybutyrate biosynthetic pathway was established in yeast through deletion of ADH6 and overexpression of yneI . Also, inspired by the mismatch of pH between host strain and key enzyme of XylD, alkaline fermentations (pH ≥ 7.0) were performed to minimize xylonate accumulation. Under the alkaline conditions, xylonate was re‐assimilated by engineered yeast and combined product yields of 3, 4‐dihydroxybutyrate and 3‐hydroxybutyrolactone resulted in 0.791 mol/mol‐xylose, which is highest compared with previous study. These results shed light on the utility of the xylose oxidative pathway in yeast. Abstract : To solve the mismatch of pH conditions between microbial host strain and heterologous enzyme of xylonate dehydratase XylD, alkaline fermentation was performed by the engineered yeast strain harboring 3, 4‐dihydroxybutyrate biosynthetic pathway. By‐product xylonate was successfully re‐assimilated and the yield of 3, 4‐dihydroxybutyrate and 3‐hydroxybutyrolactone reached at 0.791 mol/mol‐xylose.